Library Use Pattern of Undergraduate Students in Minority Degree Colleges in Andhra Pradesh - Rani, Syamalamba (DESIDOC Journal of Library & Information Technology, 2010)
Library is considered an integral component of any efficient education system. It plays an important role in the improvement of the organisation. This study, which was conducted in minority aided degree colleges, reveals the nature and the extent of use of college libraries in Andhra Pradesh. It evaluates in detail the type of material, sources and the services used by the students. It also assesses the extent of students satisfaction regarding collection, timings and library staff cooperation in finding the information. http://dx.doi.org/10.14429/djlit.29.269